Replaced by a Robot: Service Implications in the Age of the Machine. (February 2021) - McLeay, Fraser; Osburg, Victoria Sophie; Yoganathan, Vignesh; Patterson, Anthony
Service organizations, emboldened by the imperative to innovate, are increasingly introducing robots to frontline service encounters. However, as they augment or substitute human employees with robots, they may struggle to convince a distrusting public of their brand's ethical credentials. Consequently, this article develops and tests a holistic framework to ascertain a deeper understanding of customer perceptions of frontline service robots (FLSRs) than has previously been attempted. Our experimental studies investigate the effects of the (1) role (augmentation or substitution of human employees or no involvement) and (2) type (humanoid FLSR vs. self-service machine) of FLSRs under the following service contexts: (a) value creation model (asset-builder, service provider) and (b) service type (experience, credence ). By empirically establishing our framework, we highlight how customers' personal characteristics ( openness-to-change and preference for ethical/responsible service provider) and cognitive evaluations ( perceived innovativeness, perceived ethical/societal reputation, and perceived innovativeness-responsibility fit ) influence the impact that FLSRs have on service experience and brand usage intent. Our findings operationalize and empirically support seminal frameworks from extant literature, as well as elaborate on the positive and negative implications of using robots to complement or replace service employees. Further, we consider managerial and policy implications for service in the age of machines.